Iodine-rich mixed composition perovskites optimised for tin(iv) oxide transport layers: the influence of halide ion ratio, annealing time, and ambient air aging on solar cell performance. Issue 28 (2nd July 2019) - Ozaki, Masashi; Ishikura, Yasuhisa; Truong, Minh Anh; Liu, Jiewei; Okada, Iku; Tanabe, Taro; Sekimoto, Shun; Ohtsuki, Tsutomu; Murata, Yasujiro; Murdey, Richard; Wakamiya, Atsushi
Abstract : Mixed composition metal–halide perovskites were developed to improve the performance of perovskite solar cell devices incorporating tin(iv ) oxide substrates for electron transport layers by optimizing the I/Br halide ion ratio. Abstract : Iodine-rich mixed composition metal–halide perovskites were developed to improve the performance of perovskite solar cell devices incorporating tin(iv ) oxide substrates for electron transport layers by optimizing the I/Br halide ion ratio. Device performance was further enhanced by exposing to ambient atmosphere over several days, which correlated with a shift of the energy levels in the perovskite and significant suppression of charge carrier recombination. A high power conversion efficiency of 20.6% was obtained for the aged device.